2006
DOI: 10.1016/j.jacc.2005.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QTc Interval and Risk of Sudden Cardiac Death in a Population of Older Adults

Abstract: Abnormal QTc prolongation on the electrocardiogram should be viewed as an independent risk factor for sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
589
4
17

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(638 citation statements)
references
References 33 publications
28
589
4
17
Order By: Relevance
“…More importantly, ECG data obtained from radiotelemetry recording demonstrated that in vivo transfection of Ca v 2.2‐α shRNA into AVG neurons not only increased the QT interval, QTc interval, QTd, QTcd, and Tpe but also induced a spontaneous ventricular tachyarrhythmia in conscious rats (Figures 6 and 7). It has been found that prolongation of the QT and QTc intervals, increase of the QTd and QTcd (a marker of spatial heterogeneity of ventricular repolarization), and prolonged Tpe (a marker of transmural dispersion of ventricular repolarization) are associated with increased risk of malignant ventricular arrhythmias and sudden cardiac death 49, 50, 51, 52. The results in the present study provide direct evidence that blunted ventricular vagal activity increases the susceptibility to ventricular arrhythmias and induces ventricular arrhythmias.…”
Section: Discussionsupporting
confidence: 62%
“…More importantly, ECG data obtained from radiotelemetry recording demonstrated that in vivo transfection of Ca v 2.2‐α shRNA into AVG neurons not only increased the QT interval, QTc interval, QTd, QTcd, and Tpe but also induced a spontaneous ventricular tachyarrhythmia in conscious rats (Figures 6 and 7). It has been found that prolongation of the QT and QTc intervals, increase of the QTd and QTcd (a marker of spatial heterogeneity of ventricular repolarization), and prolonged Tpe (a marker of transmural dispersion of ventricular repolarization) are associated with increased risk of malignant ventricular arrhythmias and sudden cardiac death 49, 50, 51, 52. The results in the present study provide direct evidence that blunted ventricular vagal activity increases the susceptibility to ventricular arrhythmias and induces ventricular arrhythmias.…”
Section: Discussionsupporting
confidence: 62%
“…In our study, women with SCD had a mean QTc of 446±27 ms. It is important to note that healthy adult women are known to have longer QT than men; the upper limit for QTc is 450 ms for women but only 430 ms for men 22, 24. QTc of >470 ms was not predictive of SCD among women without CAD ( P =0.09), probably due to loss of statistical power in this binary specification given relatively low event rates.…”
Section: Discussionmentioning
confidence: 94%
“…Longer QTc is well known to be independently associated with SCD in men and women 6, 22. In the case‐control Oregon Sudden Unexpected Death Study of patients with CAD (40% women), QTc was longer in those with SCD compared with controls (450±45 versus 433±37 ms, P <0.0001), and abnormally prolonged QTc was associated with a 5‐fold increased risk of SCD 23.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an extensive dataset from many clinical settings has implicated QT prolongation as a predictor of subsequent mortality; these include convalescence from acute myocardial infarction, 5 diabetes, advancing age, chronic heart failure, autonomic dysfunction, hypertrophic cardiomyopathy, patients awaiting heart transplantation, antihypertensive therapy, and muscular dystrophy.…”
Section: Qt Interval Prolongation Is Associated With Arrhythmiasmentioning
confidence: 99%